Transcatheter Aortic Valve Implantation in a Nonagenarian with Aortic Aneurysm: Futility or Utility? - Evelyn Fennelly; Marcus Lee; Mark Da Costa; Sherif Sultan; Faisal Sharif; Darren Mylotte (Case Reports in Cardiology)
Transcatheter aortic valve implantation (TAVI) has emerged as the standard of care for older patients with symptomatic severe aortic stenosis (AS) at high or excessive operative risk. There remain patients that are of such considerable risk that even TAVI can be futile. Such patients present ethical conundrums for institutional heart teams. Herein we present a case of a 90-year-old female patient with symptomatic severe AS and significant comorbidities including diffuse peripheral vascular disease and a large ascending aortic aneurysm. Would TAVI be utile or futile in this patient?